FAKTOR - FAKTOR YANG MEMPENGARUHI PEMILIHAN KARIR MENJADI AKUNTAN PUBLIK OLEH MAHASISWA DEPARTEMEN AKUNTANSI FAKULTAS EKONOMI UMSU MEDAN - Maya Sari (Jurnal Riset AKuntansi dan Bisnis, 2013)
This research is purposed aim to know and analysis effected by various some factors such as toward career to Public Accountant The Accounting Major Student of Faculty of Economic at Muhammadiyah University of North Sumatera. The research sample is determined by purposive sampling with criterion that is the students of accounting department who still taking Theses proposal. The amount of sample is based on purposive sampling about 71 respondents used. The data collected is classified as primer data which is obtained by questionnaire distribution and secondary data. Data processing is conducted by using Multiple Regression Analysis.The result of this research indicate financial respect, profesional training, profesional recognation, social value, work accupation, consideration of market employ and personality to career choice of Public Accounting either it is partially and simultaneously influence with explained by variation the expressed in Adjusted R2 equal to 26.4 % is while the rest equal to 73,6% influenced by other variable which is not explained by this research model, but partially professional recognation and consideration of market employ variable has the significant influence to career choice of Public Accounting, while indicate financial respect, profesional training, social value, work accupation are not have the significant influence to career choice of Public Accounting. Profesional recognition and consideration of market employ are constitute likely of work with other expert, opportunity of branching andrecognition of achievement.